Structural analysis of cyclically periodic rings and its application to the mechanics of balloon expandable stents. (1st March 2020) - Bonfanti, Alessandra; Syngellakis, Stavros; Bhaskar, Atul
Abstract: The performance of balloon expandable stents during deployment is usually assessed computationally. Most stents have a generic feature that entails wavy rings known as "crowns" which are interconnected via structures known as "bridges". A mathematically exact analyses of such wavy rings would provide a benchmark to such computations and offer a clear insight into the deformation of stents. In the present work, an analytical model is developed to estimate the elasto-plastic response of a cylindrical periodic structure made of sinusoidal crowns interconnected by bridges. Two different interconnections are considered that give rise to two distinctive behaviours one of which is auxetic. Elastic-perfectly plastic material is considered. The apparent elasto-plastic response of the cylindrical structure is obtained in a closed-form by exploiting the periodicity along its longitudinal and the circumferential direction. A scaling ansatz is proposed that collapses nonlinear response data for different geometries into a family of master-curves. Such relationship suggests that the most efficient way to increase the apparent stiffness of the structure is to decrease the amplitude of the wavy crowns.